No rumen fermentation profiles and associated microbial diversities difference were found between Hu sheep and Karakul sheep fed a cottonseed hull diet - Jishu Wang; Guangxu E; Meng Zhang; Yanlong Zhang; Tiantian Bai; XuanXuan Pu; Junfeng Liu; Xuefeng Guo; Subir Sarker; Long Cheng (Microbiome)
Abstract Background This research aimed to investigate differences in rumen fermentation characteristics between Karakul sheep and Hu sheep reared under identical conditions. The test subjects included newborn Hu and Karakul sheep, which were monitored across three stages: stage I (Weaning period: 15 ~ 30 days), stage II (Supplementary feeding period: 31 ~ 90 days), and stage III (Complete feeding period: 91 ~ 150 days). During the supplementary feeding period, cottonseed hulls were the main roughage source. To analyze the dynamics of rumen fermentation, 16S rRNA sequencing and metabolomics methods were employed, alongside measurements of rumen fermentation parameters and cellulase activity. This comprehensive approach aimed to investigate the potential impact of breed on rumen fermentation indicators, microbial community structure, and metabolites in Hu and Karakul sheep. Results The 16S rRNA sequencing analysis revealed no significant differences in the relative abundance or dominant bacterial communities in the rumen across all stages. In stage II, rumen bacteria in both Hu and Karakul sheep were relatively stable. However, the Simpson index of Hu sheep in stage II was substantially greater than that of Karakul sheep, demonstrating similarities in the rumen microbial structure between stages II and III. Dynamic variations in fermentation parameters and cellulase activity in the rumen revealed that the indicators in both sheep breeds stabilized at 150 days. Metabolomic results revealed that the metabolic pathways in stage I were mainly concentrated in purine metabolism and lipid metabolism, while stage II was dominated by amino acid metabolism. Stage III involved mainly in pyrimidine and purine metabolism. An exploration of the relationships among rumen microbial biomarkers, key differentially abundant metabolites and rumen characteristics indicated that Karakul sheep exhibited superior lipid metabolism compared to Hu sheep. Conclusion These findings reveal that there were no interbreed differences in the rumen characteristics of Hu and Karakul sheep when fed the same cottonseed hull diet, despite differences in their metabolic pathways. The findings also indicate that the first 20 days represent the initial stage of rumen bacteria in Hu sheep, followed by a transition phase between 20 and 90 days, and a relatively stable stage from 90 to 150 days. These results provide a scientific basis for further understanding the rumen function of sheep and for optimizing their feeding strategies. Video Abstract